Cooperative Learning With Improve Type To Improve Activities And Achievements In Learning Islamic Education (PAI) - Abd Wahid Hariyono; Zainuddin Maliki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
This study aims to illustrate or describe the actual conditions of an event, namely the process of learning steps implementation applied in the classroom and students’ achievement as a result of applying the learning model namely improve type cooperative learning models in Islamic Education (PAI) subjects. This type of research is Classroom Action Research (CAR) which is a systematic study of learning practices in class that aims to fix or improve the quality and learning achievement by taking certain actions. From the results of the analysis and discussion, it can be concluded that: The Cooperative Learning Model of the Improve type is suitable to be applied to PAI subjects in class I of Vocational High School (SMK) Muhammadiyah 2 Jemundo Sidoarjo as the subject of Marriage (Munakahat). The application of learning using the Improve type cooperative learning model can be carried out well, as evidenced by an increase in each cycle. The application of the Cooperative learning model of the Improve type can improve the learning activities of the first grade students of SMK Muhammadiyah 2 Jemundo Sidoarjo. This improvement indicator is shown by the percentage of all indicators contained in the observation guide sheet of students’ learning activities observed from cycle I and cycle II. The application of the Improve type cooperative learning model can improve the learning achievement of first grade students of SMK Muhammadiyah 2 Jemundo Sidoarjo. Keywords: Cooperative Learning of Improve Type, Learning Achievement